Causes of elevated parathyroid hormone levels in postmenopausal women - Esen, İrfan and Akturk Esen, Selin and Cander, Soner and Oz Gul, Ozen and Ocakoglu, Gokhan and Erturk, Erdinc (The European Research Journal, 2017)
Objective. In this study we aimed to investigate causes of hyperparathyroidism and related factors in postmenopausal women. Methods. The study was conducted on 156 postmenopausal women, 43 with normal serum parathyroid hormone (PTH) levels and 113 with elevated serum PTH levels. Serum levels of 25-OH vitamin D, calcium and phosphorus, 24-hour urine calcium, phosphorus and calcium/creatinine ratio were compared between study groups. Also, bone mineral density, age of menopause, educational level, occupation, clothing style, daylight exposure time and daily dietary calcium consumption of subjects and relationships of these parameters with parathyroid hormone levels were investigated. Results. Causes of elevated serum PTH level were vitamin D deficiency in 92.9% and primary hyperparathyroidism in 4.4% of study group. Serum PTH levels were significantly higher in housewives (p<0.001), women with less than a high school graduates (p=0.008), and the veiled women (p=0.025). Serum 25-OH vitamin D levels were significantly lower in the veiled covered (p=0.002) and participants with less than a high school graduate (p=0.041). Significant negative correlation was detected between serum 25-OH vitamin D and the logarithmic value of serum PTH levels (r= -0.188; p=0.019). Conclusions. Vitamin D deficiency was common in all postmenopausal women but especially in those with lower education level and the veiled. Postmenopausal women should be screened for vitamin D deficiency and encouraged to benefit more from sunlight. Also, enriching foods in the markets with vitamin D may be helpful for decreasing hyperparathyroidism in this population.